Pandemonium / 2. - Oliver, Lauren, 1982- (Delirium Trilogy, 2012)
After falling in love, Lena and Alex flee their oppressive society where love is outlawed and everyone must receive "the cure"--an operation that makes them immune to the delirium of love--but Lena alone manages to find her way to a community of resistance fighters, and although she is bereft without the boy she loves, her struggles seem to be leading her toward a new love.